PEMBERDAYAAN MASYARAKAT DI SUBAK JATILUWIH KECAMATAN PENEBEL KABUPATEN TABANAN PROVINSI BALI - Amaral, Ni Putu Anglila; Sapanca, Putu Laksmi Yulianti; Ariati, Putu Eka Pasmidi (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2019)
The development of agritourism Subak in Jatiluwih village, Tabanan, Bali. The purpose of this research were to analyzed the levels of community development based on sub population farmers, local people and the operational organizer of agrotourism Subak Jatiluwih,. This research uses the method descriptive qualitative with the sample collection covering farmers as many as 25 people which determined using formula, the sample collection covering local people as many as 25 people which determined with quota sampling and the sample collection covering operational organizer as many as 25 people which determined by a method of census. The methods which used are observation, and questionnaires. The conclusion of this research is The level of community empowerment at agrotourism subak jatiluwih are still at the low at agrotourism Subak Jatiluwih is mobilize all factors of powers like the unique point of Subak, human resource potential which is supporting the development of agrotourism and then attraction Subak culture which interesting for the visitors of agrotourism Subak Jatiluwih with the chances that support agrotourism of Subak in Jatiluwih village like, market opportunity which still wide open for tourists especially especially native tourism lover.